Characterizing Solar Wind Electrons with the Core-Strahlo Model: Wind-Swe-Veis Observations - Zenteno-Quinteros, B (EDP SCIENCES S A, 2025)
Context. In this study, we apply a novel heuristic core-strahlo (CS) model to analyze solar wind electrons. This model reproduces the behavior of a core-halo-strahl representation by employing solely two subpopulations: a bi-Maxwellian core and a modified Kappa distribution that introduces skewness. This modification effectively represents halo and strahl electrons within a single skew distribution. Aims. This work aims to demonstrate that the CS model can be utilized to model observations beyond theoretical contexts. The CS model can reproduce the main features of electron velocity distribution functions (eVDFs) in the solar wind-thermal core, enhanced tails, and skewness-with the advantage that a single parameter controls the asymmetry. Methods. We implemented a comprehensive statistical analysis of solar wind electrons at 1 AU using the electron and solar wind plasma moments on board the NASA Wind SWE/VEIS instrument. This work uses a sophisticated algorithm developed to analyze and characterize separately the core and strahlo populations. We limited our effective energy from 10 eV to 3 keV and fit the eVDFs measurements observed by the WIND satellite to the CS model. Results. Our experimental analysis show good agreement with existing models of solar wind electrons, including those that account for core, halo, and strahl components, as the resulting values fall within the expected order of magnitude. The CS model not only achieves results comparable to previous studies, but also offers the added capability of accounting for heat flux and the asymmetry of the electron velocity distribution through the delta parameter, which enhances our understanding of solar wind electron dynamics. Further, we confirm that the kappa parameter (kappa) is independent of the skewness parameter (delta), consistent with previous theoretical studies findings. Conclusions. This work serves as an initial practical application of the CS model. We extend its relevance beyond theoretical contexts to the study of observational data. This novel approach not only highlights the specific dynamics of solar wind electrons but also provides insights into their behavior. Specifically, as the strahl relaxes, the halo becomes more enhanced.